2003
DOI: 10.4102/sajip.v29i4.124
|View full text |Cite
|
Sign up to set email alerts
|

Coping, stress and burnout in the South African police service in Kwazulu-natal

Abstract: The objective of this research was to determine the relationship between coping, stress and burnout in the South African Police Service. A survey design was used. The study population (N = 257) consisted of police personnel in Kwazulu-Natal. The COPE, Police Stress Inventory and Maslach Burnout Inventory – General Survey (MBI-GS), were used as measuring instruments. Structural equation analysis showed that job demands (as stressors) are associated with exhaustion. Passive coping strategies contributed to exhau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 61 publications
4
36
0
Order By: Relevance
“…In other words, the participants recognized that organizational politics played a role in stress and burnout and confirmed that the same factors that are responsible in existing literature are also reported in this study. The last objective of organizational politics, stress and burnout was addressed in this regard [47,48].…”
Section: Qualitative Discussion-organizational Politicsmentioning
confidence: 99%
“…In other words, the participants recognized that organizational politics played a role in stress and burnout and confirmed that the same factors that are responsible in existing literature are also reported in this study. The last objective of organizational politics, stress and burnout was addressed in this regard [47,48].…”
Section: Qualitative Discussion-organizational Politicsmentioning
confidence: 99%
“…However, there exists very little research on how caregivers for family members with HIV/AIDS in Kenya cope with the demands and added burden of providing care in such difficult circumstances. A search of existing literature produced several studies conducted in South Africa that utilized the Brief COPE in English only (Olley et al 2003(Olley et al , 2004(Olley et al , 2005 and the original COPE (Pienaar and Rothmann 2003;Pienaar et al 2007;Wiese et al 2003). Egisdottir et al (2008) caution against assuming that instruments developed for one culture are appropriate for use and will yield valid findings when used with a different cultural group.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (e.g. Wiese, Rothmann & Storm, 2003;Wang et al, 2014) reported a strong positive connection between job stress and occupational burnout, especially when such job-related stress is regard as oppressive and inescapable (Shane, 2010). For example, in a study involving 379 police officers, sampled from multiple police departments in the US, Russell (2014, p. 374) reported that "for every 1 percent increase in perceived stress, respondents reported nearly 12 percent increase in perceived burnout".…”
mentioning
confidence: 99%